2017
DOI: 10.1155/2017/4585424
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Taichi Softball on Function‐Related Outcomes in Older Adults: A Randomized Control Trial

Abstract: The purpose of this present study was to examine the effect of Taichi softball (TCSB) on physical function in Chinese older adults. Eighty Chinese older adults were randomly assigned into either an experimental group experiencing four 90-minute TCSB sessions weekly for seven consecutive weeks or a control group. At baseline and 7 weeks later, all participants were asked to perform physical functional tests for both lower and upper limbs. Multiple separate Analyses of Variance (ANOVA) with repeated measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 60 publications
1
23
0
1
Order By: Relevance
“…Chinese traditional Health-Qigong exercises (CTHQ) (e.g., Taichi, Baduanjin, Liu Zijue, and Wuqinxi), characterized by an integration of slow coordinating postures and musculoskeletal stretching movements, meditative mind, and breathing techniques have been extensively studied with respect to the health benefits [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Particularly, a recently published randomized controlled trial indicated that Tai-chi as one of the CTHQ was as effective as physical therapy for musculoskeletal pain management in 204 patients with knee osteoarthritis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese traditional Health-Qigong exercises (CTHQ) (e.g., Taichi, Baduanjin, Liu Zijue, and Wuqinxi), characterized by an integration of slow coordinating postures and musculoskeletal stretching movements, meditative mind, and breathing techniques have been extensively studied with respect to the health benefits [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Particularly, a recently published randomized controlled trial indicated that Tai-chi as one of the CTHQ was as effective as physical therapy for musculoskeletal pain management in 204 patients with knee osteoarthritis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implementing mind-body (MB) exercises (tai chi, qigong, and yoga) may provide a solution for this issue given that these exercises are low-cost, low impact, and of moderate-intensity [ 16 , 17 , 18 , 19 ]. MB exercises, characterized by a mind-body practice (slow movements and symmetrical postures with musculoskeletal stretching and relaxation, breath control, and mental focus), have recently increased in global popularity [ 20 , 21 , 22 , 23 , 24 , 25 ]. According to the National Health Interview Survey, Yoga, Tai Chi, and Qigong are ranked as the top three most widely-used complementary therapies among U.S. citizens [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It typically consists of a series of distinct movements called Taichi Quan, Taichi sword, Taichi fan, Taichi softball, and Taichi push hand. Such Taichi exercises share the common Chinese medicine theory and place an emphasis on a combination of physical exercise with mental focus; interaction between physical postures and movements, meditative mind, musculoskeletal relaxation and breathing techniques in a harmonious manner [ 1 ].…”
Section: Introductionmentioning
confidence: 99%